Challenges faced by L1 Shona teachers teaching English to L1 Tonga Primary School students: a case of Nenyunka Primary School. - Hungwe, Talent C. (Midlands State University, 2017)
This research project was an endeavor to map out the challenges that L1 Shona teachers faced when teaching English to L1 Tonga students with special reference to Nenyunka Primary School. The researcher used the Case Study design where she used three research instruments namely the questionnaire, interview and the observation. The research focused on 7 infant level teachers and 60 pupils from grades 1-3. The researcher gathered that there was a learning barrier between the teachers and their pupils due to the reason that their mother tongue languages were different. The researcher also gathered that due to the learning barrier, pupils developed a negative attitude towards English and also poor language use in English. The researcher recommends that the language policy on language of instruction in the teaching of infants should be practical and not a ‘paper policy’ so that children can be taught in their mother tongue. The researcher also recommends that textbooks should be written to in cooperate indigenous languages like Tonga and other minor local languages. The researcher also recommends that teachers should be trained in different local languages like Tonga, Venda, Shangani to name just a few.